The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12967-018-1562-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of endoplasmic-reticulum-stress-mediated autophagy enhances the effectiveness of chemotherapeutics on pancreatic cancer

Abstract: BackgroundEndoplasmic reticulum (ER) stress and its consequent unfolded protein response (UPR) are believed to be associated with progression, survival and chemoresistance of a variety of tumor cells through multiple cellular processes, including autophagy. Therefore, the ER stress-autophagy pathway presents a potential molecular target for therapeutic intervention. The objective of this study was to evaluate the therapeutic efficacy of ER stress and autophagy modulators in the context of pancreatic ductal ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 55 publications
4
52
0
Order By: Relevance
“…An association between hypoxia‐induced chemoresistance and autophagy is becoming increasingly apparent . Moreover, hypoxia‐associated genes and autophagy are implicated with a less favourable outcome in PDAC . PTBs are known to regulate gene expression by binding to hypoxia‐related transcripts ; therefore, we also studied the role of PTBP3 in the development of PDAC and therapeutic resistance in tumour tissue and in pancreatic cancer cell lines under hypoxic stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An association between hypoxia‐induced chemoresistance and autophagy is becoming increasingly apparent . Moreover, hypoxia‐associated genes and autophagy are implicated with a less favourable outcome in PDAC . PTBs are known to regulate gene expression by binding to hypoxia‐related transcripts ; therefore, we also studied the role of PTBP3 in the development of PDAC and therapeutic resistance in tumour tissue and in pancreatic cancer cell lines under hypoxic stress.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our results, the anti‐proliferative effect of gemcitabine was significantly increased when autophagy was inhibited. Thakur et al found that the addition of sunitinib or chloroquine to gemcitabine significantly increased survival in an animal pancreatic cancer model without an increase in toxicity. The authors proposed that sunitinib and chloroquine can reduce tumour growth through the suppression of autophagy and increased apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Autophagy is a conserved physiological process that can maintain homeostasis by degrading damaged protein and organelles, which depends on the regulation of autophagy-related protein including microtubule-associated protein light chain 3 (LC3), Beclin 1, and p62. 6,7 Autophagy is a conserved physiological process that can maintain homeostasis by degrading damaged protein and organelles, which depends on the regulation of autophagy-related protein including microtubule-associated protein light chain 3 (LC3), Beclin 1, and p62.…”
mentioning
confidence: 99%
“…For research on cancer chemotherapy, accumulating evidence has confirmed a paradoxical role of autophagy: it can act as a prosurvival or prodeath contributor to anticancer therapy. 6 Inconsequently, suppressing of autophagy enhances drug resistance in gastric cancer cells. 9 Analogously, targeting endoplasmic reticulum stress-mediated autophagy elevates the effectiveness of sunitinib and gemcitabine on pancreatic cancer.…”
mentioning
confidence: 99%